Philological Remarks on Two Genealogies of the Crimean-Tatar Clan Shirin - Göncöl Cs. (Золотоордынское обозрение)
Objectives: Philological analysis of two genealogies of the Crimean-Tatar clan termed the Shirin, and an identification of a possible common source of these genealogies. Research materials: Two genealogies (family-trees) of the most prominent clan of the Crimean Khanate, the Shirin, have survived. The earlier one was preserved in the chronicle of the ʿUmdetü l aḫbār ‘Essence of Histories’ (1748), written by ʿAbdu l Ġaffār Qırımī, a historian of the Crimean Khanate and judge on Shirin estates. The later one was presented by clan-members after 1807 to the Crimean Assembly of Nobility (Таврическое дворянское собрание) for the recognition of their noble status and estates. This version was translated into Russian and published by Lashkov. Therefore, the question arises: can the two genealogies have a common source?